A new selaginellin derivative and a new triarylbenzophenone analog from the whole plant of Selaginella pulvinata. Issue 12 (2nd December 2018) - Liu, Xin; Tang, Gui-Hua; Weng, Han-Zhuang; Zhang, Jun-Sheng; Xu, You-Kai; Yin, Sheng
Abstract: Five selaginellin derivatives (1 and3–6 ) including a new one, selaginellin T (1 ), and a new triarylbenzophenone analog, selagibenzophenone A (2 ), were isolated from the whole plants of Selaginella pulvinata . Their structures were determined by 1D- and 2D-NMR and HR-ESI-MS data. Selagibenzophenone A (2 ) is the first example of naturally occurring triarylbenzophenone. The results of the phosphodiesterase-4 (PDE4) inhibitory screening assays showed that compounds1 −6 exhibited potent activities with the IC50 values in the range of 1.04−9.35 μM. Abstract :